총기 및 폭발물에 의한 군인의 근골격계 손상: 최근 4년간 분석 - 양한별(Hanbual Yang); 황일웅(Il-Ung Hwang); 송대근(Daeguen Song); 문기호(Gi Ho Moon); 이나래(Na Rae Lee); 김경남(Kyoung-Nam Kim) (The journal of the Korean Orthopaedic Association, 2021)
목적: 현재까지 군에서 발생하는 총기 및 폭발물 손상은 그 중요성에 비해 연구된 것이 제한적이었다. 이를 극복하기 위해 최근 4 년간 총기 및 폭발물에 의해 수상한 군인 환자의 근골격계 손상에 대한 특징을 확인하고자 하였다. 대상 및 방법: 2015년 1월부터 2019년 7월까지 총기 및 폭발물에 의해 근골격계 손상을 당한 군인 환자를 대상으로 하였다. 의무기록과 의료영상저장전송시스템 영상자료를 분석하고, 전화 면담을 통해 short musculoskeletal function assessment (SMFS)를이용한 기능평가를 후향적으로 시행하였다. 기능평가에 대한 통계 분석으로 무기종류에 따른 분석은 t-test를, 다른 요인에 따른분석은 ANOVA 분석을 실시하였다. 결과: 총기 및 폭발물에 의한 손상으로 치료받은 총 61명의 환자 중 30명(49.2%)이 근골격계 손상으로 정형외과적 치료를 시행받았다. 평균 수상 나이는 26.4세(21-52세)였다. 간부와 병사의 수는 비슷하였다. 총기 손상이 11명, 폭발물 손상이 19명이었다. 30 명 중 수도병원에서 16명(53.3%)이, 민간병원에서 10명(33.3%)이 치료받았다. 12명에게 복수부위 손상이 있었고, 골절이 동반된16명(53.3%)의 환자 중 절반 이상인 7명의 환자가 다발성 골절이었다. 수부와 하퇴부가 가장 흔한 수상 부위였다. 2명을 제외하고는 모두 개방창이 있었으며, 연부조직 재건술이 필요한 환자는 14명(46.7%)이었다. SMFS 기능평가에는 15명이 응답하였다. 계급에 따른 분석 결과, Borther Index에서 간부의 결과가 통계적으로 유의하게 낮은 것으로 분석되었다(p=0.05). 치료 병원에 따른분석 결과, Dysfunction Index와 Bother Index 모두 수도병원에서 치료 받은 인원의 점수가 통계적으로 유의하게 낮은 것으로분석되었다. (p=0.0008, p=0.0149) 결론: 국내 무기에 의해 수상한 군인 환자에 대해 분석한 첫 연구이다. 무기 손상 환자의 치료에 있어 orthopedic burden이 높음을 확인하였으며, 장기적으로 이런 환자들에 대한 치료평가 및 군 외상 시스템 발전을 위해 총기 및 폭발물에 의한 손상 환자를 포함한 군 외상환자 레지스트리 구축이 필요하겠다 Purpose: To date, studies of firearm and explosive injuries in the Korean military have been limited compared to its importance. To overcome this, this study examined the characteristics of musculoskeletal damages in soldiers who have suffered firearm and explosive injuries over the past four years. Materials and Methods: From January 2015 to July 2019, military forces who had suffered musculoskeletal injuries from firearms or explosive substances were included. The medical records and radiographs were reviewed retrospectively, and telephone surveys about Short Musculoskeletal Functional Assessment (SMFA) for this group were conducted. To compare the functional outcomes, statistical analysis was performed using a t-test for the types of weapons, and ANOVA for others. Results: Of the 61 patients treated for firearms and explosives injuries, 30 patients (49.2%) were included after undergoing orthopedic treatment due to musculoskeletal injury. The average age at injury was 26.4 years old (21–52 years old). The number of officers and soldiers was similar. Eleven were injured by gunshot and 19 by an explosive device. Sixteen were treated in the Armed Forces Capital Hospital and 10 at private hospitals. More than half of the 16 patients (53.3%) with a fracture had multiple fractures. The most common injury site was the hand (33.3%), followed by the lower leg (30.0%). There were 14 patients (46.7%) with Gustilo-Anderson classification 3B or higher who required a soft tissue reconstruction. Fifteen patients agreed to join the SMFA survey for the functional outcomes. Between officers and soldiers, officers had better scores in the Bother Index compared to soldiers (p=0.0045). Patients treated in the Armed Forces Capital Hospital had better scores in both the Dysfunction and Bother Index compared to private hospitals (p=0.0008, p=0.0149). Conclusion: This is the first study to analyze of weapons injuries in the Korean military. As a result of the study, the orthopedic burden was high in the treating patients with military weapon injuries. In addition, it is necessary to build a military trauma registry, including firearm and explosive injuries, for trauma treatment evaluation and development of military trauma system. KCI Citation Count: 0